Sou professor bacharel e agora? : um guia didático para professores bacharéis - Lima, Inalda Tereza Sales de (Brasil, 2021)
T his guide is part of a master’s research developed with the Graduate Program in Technological Education of IFAM - Instituto Federal de Educação, Ciência e Tecnologia do Amazonas, which aimed to investigate how and under what professional circumstances bachelors who work in Professional Education Medium Level Technician - EPTNM constitute themselves as teachers. It should be remembered that educational products are a requirement of professional master’s degrees. In this research, which is based on the assumptions of qualitative research with a narrative approach, we interviewed six bachelors who work at EPTNM, in order to know how these professionals, work in this teaching modality they constitute themselves as teachers, considering the reasons that led them to choose to teach, the ways in which they formed themselves and the experiences lived as a teacher. With the analysis of the interviews and training memorials written by the research participants, it was possible, among other questions, to understand the difficulties they experienced in the scope of teaching. Thus, as a contribution to the bachelors who enter teaching, we chose to build, as a product educational research, this Didactic Guide, with didactic and pedagogical terms and concepts that can assist in the construction of the pedagogical knowledge of bachelors. We emphasize that the research participants collaborated with this material with suggestions of terms and reports of the difficulties they experienced at the beginning of their teaching. We hope that this guide can support the bachelor who becomes a teacher in his practice as a teacher, a challenge that is still present in the context of professional education.